2017
DOI: 10.1177/0003489417729833
|View full text |Cite
|
Sign up to set email alerts
|

Successful Placement of a BAHA Implant in a Patient With Epidermolysis Bullosa: A Case Report and Review of the Literature

Abstract: The literature regarding the otolaryngologic manifestations of EB is sparse. The otologic sequelae are particularly overlooked in the workup and management. Based on the results of this case study, it appears that an osseointegrated implant can be safely utilized to treat significant mixed or conductive hearing loss in patients with EB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, one case report 13 demonstrated success with excision of stenotic tissue, bony canal enlargement and split‐thickness skin graft. An alternative approach using a BAHA showed encouraging results for the treatment of conductive hearing loss in two patients with EB 14,15 . In the current study, we demonstrated for the first time long‐term success and feasibility of osseo‐integrated BAHA implants in two patients with RDEB‐I.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, one case report 13 demonstrated success with excision of stenotic tissue, bony canal enlargement and split‐thickness skin graft. An alternative approach using a BAHA showed encouraging results for the treatment of conductive hearing loss in two patients with EB 14,15 . In the current study, we demonstrated for the first time long‐term success and feasibility of osseo‐integrated BAHA implants in two patients with RDEB‐I.…”
Section: Discussionmentioning
confidence: 51%
“…An alternative approach using a BAHA showed encouraging results for the treatment of conductive hearing loss in two patients with EB. 14,15 In the current study, we demonstrated for the first time long-term success and feasibility of osseo-integrated BAHA implants in two patients with RDEB-I. The minimally invasive BAHA procedure (punch technique) was well tolerated in each case and accompanied by good wound healing, complication-free postoperative course and significant improvement in hearing and QoL in the follow-up periods (12 and 13 years respectively).…”
Section: Discussionmentioning
confidence: 56%
“…Surgical treatment was not considered due to the patient’s pediatric age. Brown et al 10 described the case of a patient affected by RDEB with bilateral stenosis of EACs and consequent bilateral mixed hearing. One-side surgical implantation of BAHA allowed hearing recovery.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of individuals with RDEB develops life-threatening dilated cardiomyopathy at an early age ( Fine et al, 2008 ). A less considered change is external auditory canal stenosis, which may result in hearing loss ( Brown et al, 2017 ).…”
Section: Extracutaneous Manifestations In Rdebmentioning
confidence: 99%